2-{4-[(Quinolin-8-yloxy)methyl]phenyl}benzonitrile - Wei, Bin (International Union of Crystallography, 2011)
In the title compound, C(23)H(16)N(2)O, the bond angle at the O atom that connects the benzene ring and the quinoline ring system is 116.0 (2)°. The quinoline ring system make a dihedral angle of 16.5 (2)° with the adjacent benzene ring. The dihedral angle between the biphenyl benzene rings is 70.8 (2)°.